Fertilizer management in smallholder cocoa farms of Indonesia under variable climate and market prices. (February 2020) - Hoffmann, Munir P.; Cock, James; Samson, Marianne; Janetski, Noel; Janetski, Kate; Rötter, Reimund P.; Fisher, Myles; Oberthür, Thomas
Abstract: Cocoa yields on the smallholder farms of Sulawesi are <500 kg/ha, yet, attainable yields are substantially higher. Seventy-three on farm trials were established in Sulawesi, Indonesia, to determine how farmers could optimize their fertilizer management considering both, factors under their control and factors beyond their control, such as the weather. The farmers, who were divided into four groups, had all been trained in Good Agricultural Practices (GAP). Two inorganic fertilizer regimes were compared on the farms that were all supposed to be using GAP. The trials for each group were run for 2 years, with different groups monitored over distinct periods with varying weather conditions, over a 4-year period from 2013 to 2016. Striking variations in farmer yields within groups under similar conditions were attributed to unexpectedly large variations in management. The percentage increase in yield due to fertilizer application was about 34% across all management levels and weather conditions, but the absolute yield increase was greater when weather conditions and management were favorable. Net financial returns to fertilizer applications in years with unfavorable weather and farms with poor management were negative. Rather than giving blanket fertilizer recommendations, applications should be adjusted to the level of management and the expected weather conditions. With current low levels of management, many farmers will only benefit from recommended fertilizer applications rates when weather and prices are favorable. When low prices and adverse weather are expected many farmers would be better off not applying fertilizer. Highlights: Cocoa yields were highly variable depending on management skills and weather conditions. Fertilizer input improved yields, but response was highly dependent on the farmers' skills and the prevailing weather. Availability of reliable seasonal weather forecast might play a key role in implementing successful fertilizer schemes.